Leveraging Digital Media to Enhance Students’ Spiritual Competence in Islamic Religious Education - Riha Dhatul Aisyah; Nurfadlilah Muhyi; Ngantori; Wiwin Eko Santoso (Journal of Educational Management Research, 2025)
This study aims to analyze the utilization of digital media in enhancing students’ spiritual competence in Islamic Religious Education (PAI). The research is motivated by the increasing integration of technology in education, which needs to be balanced with the reinforcement of students’ spiritual values. A qualitative descriptive approach was employed, with data collected through observations, interviews, and document analysis. The findings indicate that PAI teachers have effectively used various digital media, including instructional videos, digital Qur’an applications, and interactive platforms such as Google Classroom, Canva, and Padlet, to facilitate learning. The use of digital media was found to enhance students’ religious awareness, spiritual reflection, and learning motivation. Nevertheless, challenges remain, such as limited teacher digital literacy and internet accessibility. Overall, digital media plays a significant role in strengthening students’ spiritual competence when integrated appropriately and grounded in Islamic values. The study recommends improving teachers’ digital competencies and developing a technology-based PAI learning model that incorporates value education.